Site-directed mutagenesis of the codon for Ile-25 in gPr80env alters the neurovirulence of ts1, a mutant of Moloney murine leukemia virus TB. - Szurek, P F (1990)
ts1, a spontaneous temperature-sensitive mutant of Moloney murine leukemia virus TB, causes hind-limb paralysis in mice. A Val-25----Ile substitution in gPr80env is responsible for temperature sensitivity, inefficient processing of gPr80env, and neurovirulence. In this study, the Ile-25 in gPr80env was replaced with Thr, Ala, Leu, Gly, and Glu by site-directed mutagenesis of the codon for Ile-25 to generate a new set of mutant viruses, i.e., ts1-T, -A, -L, -G, and -E, respectively. The phenotypic characteristics of these mutant viruses differed from those of ts1. For each mutant, the degree of temperature sensitivity was correlated with the degree of inefficient processing of gPr80env, and the following rank order was observed for both parameters: ts1-E greater than ts1-G greater than ts1-L greater than ts1-A greater than ts1 greater than ts1-T. In FVB/N mice, mutant viruses of low and intermediate temperature sensitivity and inefficiency in processing of gPr80env were neurovirulent and consistently caused mutant-specific disease profiles: ts1-T caused severe whole-body tremor, ts1-A generally caused hind-limb paralysis, and ts1-L generally caused a delayed-onset paraparesis. By 150 days postinfection, FVB/N mice that were infected with ts1-G and -E, mutants of high temperature sensitivity and inefficiency in processing of gPr80env, had lymphoid leukemia instead of a neurological disease. These results suggest that the dynamics of gPr80env processing are important in determining the neurovirulent phenotype in vivo.